The limberg flap reconstruction - the optimal surgery for pilonidal sinus disease - Ramu Shapur Srihari; Appaji Mandya Naveen; Harinatha Sreekar (Our Dermatology Online, 2016)
Introduction: Pilonidal sinus disease is a common condition usually seen in young adults causing significant morbidity. Many methods have been employed for its management but are also associated with high complications. Our study analyzes the efficiency of rhomboid excision of sinus and its tract, and reconstruction with Limberg flap in the management of pilonidal sinus disease. Materials and Methods: From July 2013 to May 2015, 46 patients were operated for pilonidal sinus disease by rhomboid excision Limberg flap reconstruction in two surgical units. Duration of operation, postoperative pain, duration of hospitalization and postoperative complications were noted. The follow up was done on an out-patient basis, every month for first three months. Results: Out of 46 patients, 40 were male (86.9%) and 6 were females (13.04%). The mean age of presentation was 28 years (range 16-50 years). The operative time ranged from 40 to 75 minutes, mean operation time being 50 minutes. Hospitalization ranged from 3-5 days, drains were removed on postop day 2/3. The stitches were removed after 12-14 days. Four patients developed mild infection. One patient developed necrosis at the tip of the flap. One patient developed recurrent lesion after 4 months, which may be due to improper excision of the sinus. The time off-work ranged from 12 to 22 days. The mean follow-up period was 3 months. Conclusion: Limberg flap is very effective for pilonidal disease with comparatively fewer complication, short hospitalization, lesser rates of reoccurrence, early healing and lesser time off-work. The technique can be mastered easily and provides an effective procedure for primary as well as recurrent disease. The results of this study support the wide excision and Limberg flap rotation as a preferred treatment of the disease.